2014
DOI: 10.1037/a0036039
|View full text |Cite
|
Sign up to set email alerts
|

The psychology of spite and the measurement of spitefulness.

Abstract: Spite is an understudied construct that has been virtually ignored within the personality, social, and clinical psychology literatures. This study introduces a self-report Spitefulness Scale to assess individual differences in spitefulness. The scale was initially tested on a large sample of 946 college students and cross-validated on a national sample of 297 adults. The scale was internally consistent in both samples. Factor analysis supported a 1-factor solution for the initial pool of 31 items. Item respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 70 publications
7
114
0
1
Order By: Relevance
“…One week before the experimental session, all the registered participants received an email with a personal code and a link to two online tasks—the risk preferences test by Gneezy and Potters () and the Social Value Orientation (SVO) Slider Measure by Murphy, Ackermann, and Handgraaf ()—to be completed at least 24 hr before the laboratory session. These tests were followed by an unrelated psychological questionnaire—a 17‐item Spitefulness Scale by Marcus, Zeigler‐Hill, Mercer, and Norris ()—so as to cloud the expectations that the participants could have formed about the tasks in the experimental session . These tasks were incentivized and presented in random order.…”
Section: Methodsmentioning
confidence: 99%
“…One week before the experimental session, all the registered participants received an email with a personal code and a link to two online tasks—the risk preferences test by Gneezy and Potters () and the Social Value Orientation (SVO) Slider Measure by Murphy, Ackermann, and Handgraaf ()—to be completed at least 24 hr before the laboratory session. These tests were followed by an unrelated psychological questionnaire—a 17‐item Spitefulness Scale by Marcus, Zeigler‐Hill, Mercer, and Norris ()—so as to cloud the expectations that the participants could have formed about the tasks in the experimental session . These tasks were incentivized and presented in random order.…”
Section: Methodsmentioning
confidence: 99%
“…Marcus, Zeigler‐Hill, Mercer, and Norris () recently developed a self‐report spitefulness scale. In the initial validation samples, this scale was moderately correlated with measures of the Dark Triad personality traits.…”
Section: Spitefulnessmentioning
confidence: 99%
“…In addition, Miller et al (2010) suggested that researchers consider a second constellation of personality features that were both dark and emotionally vulnerable, which they referred to as the Vulnerable Dark Triad (i.e., borderline personality features, vulnerable narcissism, and secondary psychopathy). We are supportive of attempts to broaden the examination of dark personality features beyond those included in the Dark Triad (or recent expansions such as the Dark Tetrad or Vulnerable Dark Triad), including characteristics that have received relatively little previous attention, such as spitefulness (Marcus, Zeigler-Hill, Mercer, & Norris, 2014) and statusdriven risk taking (Visser, Pozzebon, & Reina-Tamayo, 2014). However, we believe that it is simply too early in the process of understanding these dark personality features to attempt to identify the precise number of dark personality features that exist.…”
Section: Research Concerning the Dark Triadmentioning
confidence: 68%